The Vikings on film : essays on depictions of the Nordic Middle Ages - Harty, Kevin J. (McFarland, 2011)
"Essays discuss American, British and European productions. Analyzed in detail are such films as The Vikings (1958), The Long Ships (1964), Alfred the Great (1969), Erik the Viking (1989) and Outlander (2008), and a pair of comic-strip adaptations, the live-action Prince Valiant (1997) and the animated Astérix and the Vikings (2006). Comprehensive filmography included"--Provided by publisher.